Dilema Pemenuhan Kebutuhan Pengguna Layanan dalam Praktek Pelayanan Publik - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; SRI ROEKMINIATI (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Improving the quality of service is one of the crucial issues in the implementation of management, both in public sector management and private sector. The persistently high level of service user complaints shows that the government as public organizations are still not fully able to create a system acceptable service in the eyes of the people. Along with this there are several government programs related to the fulfillment of public service but not in accordance with the needs of the community or in its implementation still have many problems. This is a dilemma that needs to be assessed and sought alternative solutions. Such circumstances make the community as users of public services to be not satisfied, so that people are reluctant to take care of everything related to government bureaucracy. Next community finding shortcuts in a way violating the existing rules, this is where the process of corruption, collution, and nepotism begins. Services become commodities that are bought and sold by the apparatus to enrich themselves, bargaining occurs in the provision of services to the community that should have a duty and responsibility.